The economic burden of injury: Health care and productivity costs of injuries in the Netherlands - Polinder, Suzanne; Haagsma, Juanita; Panneman, Martien; Scholten, Annemieke; Brugmans, Marco; Van Beeck, Ed (Accident analysis and prevention, 2016)
•The total costs per injury patient were €4,300; €2,500 direct health care costs and €1,800 productivity costs per patient.•We identified known risk groups (elderly females with hip fractures resulting from falls) for high costs.•Less obvious risk groups are children falling from furniture, males with soccer injuries and bicycle injuries (all ages).•Health care costs were higher in females, whereas males have more than twice as high productivity costs. Detailed information on health care costs and productivity costs for the whole spectrum of injuries is lacking. We measured the total costs of injuries by external-cause, injury groupings, age and sex. Injury patients visiting an Emergency Department in the Netherlands were included. Health service use and work absenteeism were estimated with national database data and a prospective follow-up study. Health care costs (direct costs) and productivity costs (indirect costs) were determined using the incidence-based Dutch Cost of Injury Model. Total costs of injuries were €3.5 billion annually (€210/capita and €4300/patient); €2.0 billion healthcare costs and €1.5 billion productivity costs. Home and leisure injury subcategory falls caused 41% of total costs. Traffic injury was prominent in the 15–54 age group, mainly due to bicycle injuries. Sports injuries, in special football/soccer injuries, resulted in high costs in the 15–24 age group. Although costs per patient were comparable between males and females, health care costs were higher in females, whereas males have more than twice as high productivity costs. Health care costs were highest for hip fractures (€20,000/patient). Extremity fractures had high costs due to high incidences and high productivity costs per patient. Our detailed cost model identified known risk groups, such as elderly females with hip fractures resulting from falls, as well as less obvious important high risk groups, such as young children falling from furniture, young males who sustained football/soccer injuries and bicycle injuries among all ages. This information is essential to assess additional priority areas for prevention.